Evaluation of maxillary 1st premolar root morphology - M Ketabi; M Mahabadi; V Esfahanian (Isfahan University of Medical Sciences, 2008)
Introduction: Periodontal diseases are among the most common diseases of the oral cavity.Different predisposing factors are responsible for initiation of these diseases. One of these factorsis difficulty to access the area of plaque accumulation due to morphologic and anatomic variations.The aim of this study was to determine the anatomic and morphologic properties of the root ofmaxillary 1st premolar.Methods and materials: The root morphology of 162 randomly collected first maxillary premolarswas studied. The general characters of the collected teeth including number and length of the roots,length of root trunk, location of furcation in 2 rooted teeth, and the direction of root curvature weredetermined. Then the roots were sectioned and mean of concavity depth on different root surfaceswere measured using stereomicroscope with 32 magnifications. These means were measured in themesial and distal surfaces of the teeth. The topography of furcation area was also found by asection given 2 mm apical from furcal furnix.Results: 66.6% of teeth were single, 31.48% double and 1.85% were triple rooted. In most of 2rooted teeth, furcation area was located in the middle third of the root. Palatal concavity of buccalroot was a common finding in 2 rooted teeth and a significant relation between the concavity, itsdepth and the location of the furcal area was found. In comparison, the depth of mesial concavityon different surfaces was more than distal concavities. In single rooted teeth, the concavity depthwas lower in the middle than the cervical third. In 17.64% of 2 rooted teeth, the width of furcationentrance was smaller than standard gracy curettes.Discussion: Morphologic properties of teeth are not necessarily similar in different population.Therefore, these differences must be considered in dental and periodontal treatment protocols.Keywords: Maxillary first premolar, Root, Anatomy, Morphology